Greenhouse Gas Payback Time of Different HVAC Systems in the Renovation of Nordic District-Heated Multifamily Buildings Considering Future Energy Production Scenarios - Alaa Khadra; Jan Akander; Jonn Are Myhren (Buildings, 2024)
The European Union (EU) has implemented several policies to enhance energy efficiency. Among these policies is the objective of achieving energy-efficient renovations in at least 3% of EU buildings annually. The primary aim of this study was to offer a precise environmental comparison among four similar district-heated multifamily buildings that have undergone identical energy efficiency measures. The key distinguishing factor among them lies in the HVAC systems installed. The chosen systems were as follows: (1) exhaust ventilation with air pressure control; (2) mechanical ventilation with heat recovery; (3) exhaust ventilation with an exhaust air heat pump; and (4) exhaust ventilation with an exhaust air heat pump with a Photovoltaic (PV) panel. This study involved a life cycle assessment that relied on actual material data from the housing company and energy consumption measurements. This study covered a period of 50 years for thorough analysis. A sensitivity analysis was also conducted to account for various future scenarios of energy production. The findings revealed that the building with an exhaust air heat pump exhibited the lowest greenhouse gas emissions and the shortest carbon payback period (GBPT), needing only around 7 years. In contrast, the building with exhaust ventilation without heat recovery showed the highest emissions and the longest carbon payback period (GBPT), requiring approximately 11 years. Notably, the results were significantly influenced by future scenarios of energy production, emphasizing the crucial role of emission factors in determining the environmental performance of distinct renovation scenarios.